2005
DOI: 10.1111/j.1939-1676.2005.tb02783.x
|View full text |Cite
|
Sign up to set email alerts
|

Uroperitoneum in 32 Foals: Influence of Intravenous Fluid Therapy, Infection, and Sepsis

Abstract: Foals may present to a referral hospital with the primary diagnosis of uroperitoneum (UP), or they may develop UP while hospitalized for other reasons. Historical, physical, laboratory, and diagnostic variables of foals presenting with UP were compared to those developing UP while hospitalized. Emphasis was placed on the presence of electrolyte abnormalities, evidence of sepsis or infection, and development of anesthetic complications during surgical correction of the defect. Foals developing UP while in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 10 publications
(9 reference statements)
0
22
0
Order By: Relevance
“…Concomitant uroperitoneum and septicemia is a well described condition, but few investigations have shown that septicemia can be the direct causative effect of uroperitoneum in equine neonates, although it appears to be an important predisposing factor for the development of uroabdomen (Dunkel et al, 2005). In septic foals, E. coli and Actinobacillus equuli are the most commons organisms isolated from culture of the blood; while E. coli and Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant uroperitoneum and septicemia is a well described condition, but few investigations have shown that septicemia can be the direct causative effect of uroperitoneum in equine neonates, although it appears to be an important predisposing factor for the development of uroabdomen (Dunkel et al, 2005). In septic foals, E. coli and Actinobacillus equuli are the most commons organisms isolated from culture of the blood; while E. coli and Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…An association between the development of uroperitoneum and hypoxic insults, infection and sepsis has been suggested (Dunkel et al 2005). The classic electrolyte abnormalities associated with the condition, namely hyponatraemia, hypochloraemia and hyperkalaemia may not be observed in foals receiving intravenous fluid therapy and the disease may only manifest as increased serum creatinine concentration and sudden decrease in urine production (Dunkel et al 2005, Kablack et al 2000. Diagnosis is best established by ultrasonographic examination of the abdomen.…”
Section: Fenoldopammentioning
confidence: 99%
“…Nevertheless, attempts are occasionally been made to selectively improve renal perfusion. Post renal failure must be ruled out in any critically ill neonate with decraeser urine output, as it may develop during hospitalization, as discussed below (Dunkel et al 2005, Kablack et al 2000.…”
Section: Support Of Renal Functionmentioning
confidence: 99%
“…2002). In neonates the condition is more common in colts (Hackett 1984), and may be associated with dystocia (Dunkel et al . 2005).…”
mentioning
confidence: 99%